Etiology of early onset septicemia among neonates at the University College Hospital, Ibadan, Nigeria - Abimbola Ellen Akindolire; Olukemi Tongo; Hannah Dada-Adegbola; Olusegun Akinyinka (Journal of Infection in Developing Countries)
Introduction: Neonatal septicemia remains a major cause of newborn deaths in developing countries. Its burden is further compounded by the emergence of multidrug-resistant pathogens, which is related to a lack of antibiotic protocols resulting in unrestricted use of antibiotics. The absence of reliable antibiotic sensitivity testing makes the formulation of antibiotic guidelines and judicious use of antibiotics difficult. This study sought to identify the current bacterial agents associated with early onset septicemia (EOS; age <72 hours) and their antibiotic susceptibility patterns among neonates at the University College Hospital, Ibadan, Nigeria. Methodology: A total of 202 inborn and outborn neonates with risk factors for or clinical features of septicemia in the first 72 hours of life had samples for blood cultures and antibiotic sensitivity patterns taken prior to treatment. Results: Of the subjects, 95 (47.0%) were inborn and 107 (53.0%) outborn, with a M:F ratio of 1.3:1; 12.5% were culture positive, and the prevalence of EOS was 8.8/1,000 live births. The isolates were Staphylococcus aureus (52%), 30.7% of which were methicillin-resistant Staphylococcus aureus (MRSA), Klebsiella pneumoniae (12%), Enterobacter aerogenes (8%), Enterococcus spp. (8%), Eschericia coli (4%), and other Gram-negatives (12%). All the isolates except Staphylococcus aureus were susceptible to ampicillin, ampicillin/sulbactam, amikacin, gentamicin, and third-generation cephalosporins. All MRSA were sensitive to amikacin, ciprofloxacin, and chloramphenicol, while all methicillin-sensitive Staphylococcus aureus were sensitive to ampicillin/sulbactam. Conclusions: Staphylococcus aureus was the commonest cause of EOS in our setting, with 30.7% of the Staphylococcus aureus isolates being MRSA. Only MRSA demonstrated multidrug resistance.